Survey on maloccluslon in Iraqi dental student sample (Mustansiria Dental Journal, 2024)
The aim of this survey is to investigate the prevalence of malocclusion anddifferent morphological features of dental occlusion in an Iraqi sample. The sampleconsisted of (218) dental student at college of Dentistry, Baghdad university, aged (18-21year) & of both sexes. Were clinically evaluated after exclusion of students who havereceived any type of orthodontic treatment. The students also divided into two groups, thegroup who have received extraction of any tooth and the other group who have noextraction. Ag,Of the sample (26.14%) had normal occlusion, (6o)05%) had CL.l malocclusionhad CL.II malocelusion and (0.45%) who had CLIII malocclusion. The )%3,77(differences in prevalence of maloeclusion was statistically significant between thesegroups. On the other hand. This statistical difference was significant in eases withextraction than those cases without extraction (P< 0.05). clearly, there is a need forfurther epidemiologeal research aiming to increase the knowledge a bout the prevalenceand type of malocclusion as well as the extent of need & demand for orthodontic treatment.